BIOM-09. GUIDING PRECISION THERAPEUTICS THROUGH INTERROGATING ONCOGENIC PATHWAY ACTIVATION. (14th November 2022) - Nobre, Liana; Levine, Adrian; Milos, Scott; Johnson, Monique; Laxer, Ben; Ryall, Scott; Bennett, Julie; Ku, Michelle; Siddaway, Robert; Tabori, Uri; Hawkins, Cynthia
Abstract: The deregulation of canonical oncogenic pathways are largely responsible for driving pediatric cancers and can be targeted for therapeutics. Currently, we interrogate these pathways clinically by looking for gene mutations, but these are not found in all cases, and in others multiple genes are. We hypothesized that assessing transcriptomic and proteomic-based pathway activation will allow a better understanding of the most active oncogenic pathways and help guide therapy. To do this, we developed and validated a nanostring based assay that interrogates 4 key actionable pathways (MAPK, PI3K-AKT-mTOR, JAK-STAT, and NFkB) including RNA, protein and phosphoprotein expression. The assay was clinically validated using isogenic cell lines and a cohort of 40 gliomas with previous RNAseq. We then interrogated over 400 tumor samples, including 15 ependymomas, 11 medulloblastomas, 250 low grade gliomas (LGG), 145 high grade gliomas and 10 control normal brain specimens. Interestingly, although pediatric LGG exhibited higher MAPK activation than control tissue and other tumor types, a subset of these tumors have increased activity in PI3K, JAK and NFKB pathways. Furthermore, high PI3K activation score was correlated with worse PFS in a subset of pediatric LGGs that required adjuvant chemotherapy (p=0.018). To further explore the therapeutic implication of the assay, we analyzed a cohort of patients treated with MEK inhibitors (n=20). Strikingly, on top of universal RAS/MAPK activation, crosstalk between additional activated pathways such as PI3K and JAK-STAT may contribute to lack of response. In particular, pre-treatment and post-progression PLGG who failed therapy, revealed mild reduction in MAPK signature accompanied by increased PI3K phospho-proteins (p-S6/p-4EBP1, p-AKT)(p< 0.01). We conclude that assessing oncogenic pathway activation can add to DNA sequencing to predict different outcome and response to targeted therapies in childhood brain tumors. This can inform future therapeutic strategies including the identification of potential responders and combination strategies for non-responders.